1974
DOI: 10.1073/pnas.71.9.3565
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Immunity Against Rous Sarcomas of Chickens. Preferential Reactivity Against Autochthonous Target Cells as Determined by Lymphocyte Adherence and Cytotoxicity Tests In Vitro

Abstract: Spleen cells from random-bred chickens bearing Rous sarcomas were commonly more reactive against the neoplastic target cells'in autochthonous than in allogeneic interactions in vitro. This difference was observed both in cytotoxic assays (hCr release from labeled target cells) and in an immunoadherence test measuring attachment of $"Cr-labeled splenocytes to Rous sarcoma cells. Specific splenocyte reactivity was not observed with normal embryonic chicken fibroblasts, 3T3 cells, or embryonic mouse C3H fibro'bla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

1975
1975
1986
1986

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(26 citation statements)
references
References 16 publications
2
24
0
Order By: Relevance
“…with suspensions of either autochthonous or allogeneic sarcoma cells prior to use in a " crisscross " experiment (Wainberg et al, 1974) (Fig. 4).…”
Section: Efect Of Absorption Of Sera On Tumor-cell Inimunofluorescencementioning
confidence: 99%
See 1 more Smart Citation
“…with suspensions of either autochthonous or allogeneic sarcoma cells prior to use in a " crisscross " experiment (Wainberg et al, 1974) (Fig. 4).…”
Section: Efect Of Absorption Of Sera On Tumor-cell Inimunofluorescencementioning
confidence: 99%
“…
Complement-mediated cytotoxicity and indirect immunofluorescence assays showed that sera from random-bred chickens bearing Rous sarcoma ( R S)At least two distinct cell-surface antigens have been associated with chicken cells transformed by the Rous sarcoma virus (RSV): a virus sub-group-specific envelope antigen and an avian leukosis virus group-specific tumorassociated antigen (Gelderblom et al, 1972; Kurth and Bauer, 1972a, b).We have previously reported that splenocytes from randomly-bred Rous sarcoma-bearing chickens are specifically reactive against primary cultures of tumor cells (Wainberg et al, 1974). This was demonstrated by measuring both the immune adherence of 51Cr-labelled splenocytes to the neoplastic cells in vitro, and the capacity of the spleen cells to induce release of %r from labelled Rous sarcoma target cells.
…”
mentioning
confidence: 96%
“…General applicability of this observation to other or all RSV tumor systems will be the subject of further investigation. The presence of such a unique antigen in RSV-induced chicken tumors has been indicated by the work of Wainberg et al (48). Moreover, Collins and Black (44) have described the occurrence of unique individual-specific antigens in SV 40-transformed hamster cells.…”
Section: Discussionmentioning
confidence: 92%
“…In addition, Mitchison [21], Thomas [22] and particularly Lawrence [-23] drew parallels between the transplantation reaction, i. e., the cellular immune response against tissue grafts expressing foreign MHC antigens and delayed type hypersensitivity against intracellular parasites or ocontact allergens. The similarity between these two cell-mediated immune reactions was formally demonstrated by the discovery that T cells involved in syngeneic immune functions express two types of specificities: One for self-antigens coded for by the MHC (//-2 in mice [-24-30], H L A in humans [, [31][32][33][34], AgB in rats [35], B in chickens [36,37]) and a second one for the foreign non-self antigen (X) (Reviewed in [38,39]). 1…”
Section: Thymus Dependence and Dual Specificity Of T Cellsmentioning
confidence: 99%